Mental health experiences of mothers in Jos, Nigeria: An interpretative phenomenological analysis. (April 2021) - Jidong, Dung Ezekiel; Husain, Nusrat; Francis, Christopher; Murshed, Maisha; Roche, Ayesha; Ike, Tarela J; Karick, Haruna; Dagona, Zubairu K; Pwajok, Juliet Y; Nyam, Pam P; Mwankon, Shadrack B; Gumber, Anil
Objectives: There is an increasing mental health disease burden in mothers with infants and young children, especially in low- and middle-income countries such as Nigeria. Children of distressed mothers suffer early-life exposure from the effects of maternal distress which contributes to the risk of physical and mental health problems in their childhood and beyond. This study explored mental health lived experiences of mothers in Jos, Nigeria. Methods: Purposive and Snowball sampling techniques were adopted, and a total of 40 mothers participated with 8 to 11 participants in one of the four focus group discussions. Participants were between the ages of 18 and 43 years, self-identified as mothers with each having a child between the ages of 3 and 48 months. Each focus group lasted approximately 60 minutes and was audio-recorded. Interviews were transcribed verbatim and analysed using interpretative phenomenological analysis. Results: Three overarching themes emerged from the data set such as (1) experience of persisting psychological distress from the time of labour/birth; (2) cultural practices that influence feelings; and (3) anxiety due to limited knowledge about childcare, access to support and healthy food. Conclusion: Maternal mental health in Nigeria is under-researched and distressed mothers have limited knowledge about evidence-based early child development. The study recommends developing and testing culturally appropriate parenting interventions in Jos, Nigeria. This is likely to be beneficial for the mother and may also improve child health outcomes.